Nos années 80. (Jouy-en-Josas : Fondation Cartier, 1989)
Autard, Georges ; Baqué, Richard ; Bartolani, Judith ; Caillol, Claude ; Baumann, Arnaud ; Ravel, Yves ; Birkemeyer, Hans ; Blais, Jean-Charles ; Blanchard, Rémi ; Blocher, Sylvie ; Boisrond, François ; Calle, Sophie ; Chevalier, Miguel ; Cognée, Philippe ; Collin-Thiebault, Gérard ; Combas, Robert ; Couturier, Marc ; Dalbis, Eric ; Delprat, Hélène ; Di rosa, Hervé ; Domage, thierry ; Ducaté, Marie ; Faucon, Bernard ; Favier, Philippe ; Garouste, Gérard ; Gauthier, Dominique ; Le Groumellec, Loïc ; Jammes, ouis ; Joubert, Laurent ; Laget, Denis ; Leccia, Ange ; Lévêque, Claude ; Monnier, Richard ; Othoniel, Jean-Michel ; Perrodin, François ; Picasso, Kiki ; Pierre et Gilles ; Rousse, Georges ; Stenger, Nicole ; Traquandi, Gérard ; Tremblay, Daniel ; Turpault, Alain ; Valay, Florence
Nos années 80, Fondation Cartier, Jouy-en-Josas, 16 juin - 5 novembre 1989
boek